2021
DOI: 10.47081/njn2021.12.1/001
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Experimental Model of Konzo: Characterization of Motor Impairment and Neurodegeneration after Cassava Neurotoxicity in the Rat

Abstract: Konzo is a motor neuron neurodegenerative disease caused by bitter cassava toxicity that presents as a non-progressive spastic paraparesis. The ability of bitter cassava to produce behavioural and structural changes in adult rat nervous system was examined. Twenty five rats were used for this study, and pruned to 20 after consistent baseline performance was achieved (n=20; control=5, cassava chow=15). The rats were switched to a cassava diet for another 5 weeks (n=15). After the cassava consumption period, 5 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This group were the first to demonstrate cognitive impairment with konzo [3,4], after earlier electroencephalographic studies suggested cortical involvement [1,5]. Not much study has been carried out on konzo disease using animal models, but in recent times, a neuroscience researcher in Nigeria, David Lekpa Kingdom, has been carrying out in-vivo study into the neurological effect of bitter cassava induced konzo disease using rat models to better understand the mechanism in which konzo affects the neural system [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This group were the first to demonstrate cognitive impairment with konzo [3,4], after earlier electroencephalographic studies suggested cortical involvement [1,5]. Not much study has been carried out on konzo disease using animal models, but in recent times, a neuroscience researcher in Nigeria, David Lekpa Kingdom, has been carrying out in-vivo study into the neurological effect of bitter cassava induced konzo disease using rat models to better understand the mechanism in which konzo affects the neural system [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%